IL-33 and ST2 levels in chronic kidney disease: Associations with inflammation, vascular abnormalities, cardiovascular events, and survival. - Ozkan Gungor; Hilmi Umut Unal; Aydin Guclu; Mustafa Gezer; Tayfun Eyileten; Fatma Betül Guzel; Orcun Altunoren; Ertugrul Erken; Yusuf Oguz; Ismail Kocyigit; Mahmut Ilker Yilmaz (PLoS ONE)
Objective Increased inflammation, associated with the increase in chronic kidney disease (CKD) stage, has a very important influence in vascular injury and cardiovascular diseases. In this study, we aimed to investigate the levels of IL-33 and ST2 in the different stages of CKD and to determine their effect on vascular damage and cardiovascular events (CVE). Methods This was an observational cohort study in which serum IL-33 and ST2 were obtained from 238 CKD (stages 1-5) patients. We examined the changes in IL-33/ST2 levels in CKD patients, as well as the association with a surrogate of endothelial dysfunction. Fatal and non-fatal CVE were recorded for a mean of 24 months. We also performed a COX regression analysis to determine the association of IL-33/ST2 levels with CVE and survival. Results IL-33 and ST2 levels were significantly increased and estimated glomerular filtration rates (eGFR) were decreased. Flow-mediated dilatation (FMD) was significantly decreased from stage 1 to stage 5 CKD. IL-33 and ST2 levels were associated with FMD, and ST2 was a predictor. Multivariate Cox analysis showed that the presence of diabetes mellitus, smoking, and proteinuria and haemoglobin, Hs-CRP, IL-33, and ST2 were associated with the risk of CVE. Kaplan-Meier survival curves showed that patients with IL-33 and ST2 levels below the median value (IL-33 = 132.6 ng/L, ST2 = 382.9 pg/mL) had a higher cumulative survival compared with patients who had IL-33 and ST2 levels above the median value (log-rank test, p = 0.000). Conclusion This is the first study that demonstrates that serum IL-33 and ST2 are associated with vascular injury, cardiovascular events, and survival in CKD patients.